2006
DOI: 10.4161/psb.1.5.3390
|View full text |Cite
|
Sign up to set email alerts
|

Gluconoacetobacter diazotrophicusElicitate a Sugarcane Defense Response Against a Pathogenic BacteriaXanthomonas albilineans

Abstract: A new role for the plant growth-promoting nitrogen-fixing endophytic bacteria Gluconacetobacter diazotrophicus has been identified and characterized while it is involved in the sugarcane-Xanthomonas albilineans pathogenic interactions. Living G.diazotrophicus possess and/or produce elicitor molecules which activate the sugarcane defense response resulting in the plant resistance to X. albilineans, in this particular case controlling the pathogen transmission to emerging agamic shoots. A total of 47 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…G. diazotrophicus potentially possesses and/or produces elicitor molecules, which activate the sugarcane defense response. Transcripts showed significant homologies to genes of the ethylene signaling pathway (26%), proteins regulates by auxins (9%), β-1,3 Glucanase proteins (6%) and ubiquitin genes (4%), all major signaling mechanisms, support this hypothesis (Arencibia et al, 2006).…”
Section: Introductionmentioning
confidence: 82%
“…G. diazotrophicus potentially possesses and/or produces elicitor molecules, which activate the sugarcane defense response. Transcripts showed significant homologies to genes of the ethylene signaling pathway (26%), proteins regulates by auxins (9%), β-1,3 Glucanase proteins (6%) and ubiquitin genes (4%), all major signaling mechanisms, support this hypothesis (Arencibia et al, 2006).…”
Section: Introductionmentioning
confidence: 82%
“…In addition, the sugarcane endophytic diazotrophs may promote growth by indirect pathways. G. diazotrophicus has antagonistic potential against sugarcane pathogens like Collectotrichum falcatum, the red rot fungal pathogen (Muthukumarasamy et al 2000) and Xanthomonas albilineans, the causative agent of leaf scald disease (Blanco et al 2005;Arencibia et al 2006;Saravanan et al 2008). This antagonistic activity may prevent the deleterious effects of the pathogen and consequently, promote plant growth.…”
Section: Beneficial Features Of the Associationmentioning
confidence: 99%
“…This pathogenic bacterium secretes a xanthan gum that occupies both xylem and phloem of the host (Blanco et al 2005). cDNA-AFLP analysis was carried out to evaluate the potential of G. diazotrophicus colonization to protect sugarcane against X. albilineans, and this study identified several plant genes candidate to be involved in this process (Arencibia et al 2006). The results suggested that sugarcane inoculation with G. diazotrophicus can trigger mechanisms via defenserelated genes activation, such as the ethylene pathway, which elicitate plant defense protection against other pathogens attack.…”
Section: Sugarcane Defense Responsesmentioning
confidence: 99%
“…Endophytes might also induce resistance responses in the host plant which protect it from pathogens and pests. In sugarcane the endophytic nitrogen-fixing bacterium Gluconacetobacter diazotrophicus induces resistance to the leaf scald pathogen, Xanthomonas albilineans (Arencibia et al 2006). Plant genotype can influence the likelihood and extent to which a plant will become colonized by an endophyte indicating that breeding and selecting sugarcane for endophyte colonization has potential.…”
Section: Can Plants Use Microbes As Bodyguards?mentioning
confidence: 99%